Unwise Criminal Environmental Law Policies In Protecting Aceh’s Customary Forests From Destruction - Muhammad Natsir; Ferdi Ferdi; Muh. Din; Akmal Handi Ansari Nasution; Zaki Ulya (Journal of Law and Legal Reform, 2026)
This study critically examines the ineffectiveness of environmental criminal law policies in protecting Aceh’s customary forests from ongoing destruction. Although Indonesia has established a comprehensive legal framework for environmental protection, deforestation within customary forest areas in Aceh persists, indicating weaknesses in policy implementation and enforcement. This research aims to analyze the structural and normative factors that render environmental criminal law policies ineffective, particularly the lack of integration between state law and Aceh’s customary law. Employing a qualitative socio-legal approach, this study draws on statutory analysis, literature review, in-depth interviews, and field observations within customary forest areas in Aceh. The findings reveal that weak intergovernmental coordination, limited recognition of indigenous forest rights, inadequate law enforcement capacity, and minimal utilization of monitoring technology contribute significantly to forest degradation. Furthermore, the disconnect between formal environmental criminal law and customary forest governance undermines community participation and legal effectiveness. This study argues that current policies remain “unwise” because they prioritize punitive approaches without incorporating customary law values and restorative ecological justice. As a policy solution, the study proposes an integrative framework that harmonizes environmental criminal law with Aceh’s customary law, supported by restorative sanctions and technology-based forest monitoring systems. Strengthening indigenous participation and aligning national regulations with local legal traditions are essential to enhancing legal effectiveness and sustainable forest governance. This research contributes to environmental legal scholarship by offering a contextualized model of pluralistic environmental criminal law reform in Indonesia.